An Interview Survey: Knowledge on CSDS Among Chemistry Teachers at Secondary Schools in Kubang Kerian, Kelantan, Malaysia'' - Abdul Basir, Haji Ahmad (Universiti Sains Malaysia, 2006)
Lack of knowledge or awareness in dealing with chemicals substances in laboratory may potentially lead to chemical accidents at workplace which may contribute towards major injuries or damages especially among school children in school laboratory. This study quantified how well the knowledge of Material Safety Data Sheet (MSDS) or Chemical Safety Data Sheet (CSDS) and determined understanding of MSDS/CSDS and their practice of obeying the regulation stated in Classification, Packaging and Labeling {CPL) Regulation 1997 among chemistry teachers in secondary schools in Kubang Kerian and to determine training needs in chemical safety at schools. Face to face interview survey was done among chemistry teachers consist of six respondents from five schools in Kubang Kerian district using standard questionnaires base on CPL Regulation 1997. None of the respondent knows about MSDS/CSDS or aware about CPL 1997 and there is no specific training in chemical safety even though they are dealing with hazardous chemicals in the laboratory. However, most of them know parts of the dangerousness of the chemicals from the labels. A very useful information was obtained in the study that can be used by various departments for training and preventive programs at school level for the MSDS/CSDS system to be implemented effectively and thereby protect staffs and school children from the harmful effects of the hazardous chemicals.